Empowerment of Muslim Women through Microfinance and Self Help Groups: A Case Study of Chennai City - Jamal, M. Abdul; Raihana, Amatul Khadir Ayesha; Sultana, H. Yasmeen (Asian Business Review, 2016)
The empowerment of women is one of the central issues in the process of development of countries all over the world. The Government of India has made Empowerment of Women as one of the principal objectives of the Ninth Five Year Plan (1997-2002) and also declared 2001 as the year of ‘Women’s Empowerment’. Women’s empowerment is a process in which women gain greater share of control over resources - material, human and intellectual like knowledge, information, ideas and financial resources like money - and access to money and control over decision-making in the home, community, society and nation, and to gain `power’. Microfinance is the provision of small amounts of financial services to low income poor and very poor self employed people. The participation of women in Self Help Groups (SHGs) made a significant impact on their empowerment both in social and economical aspects. This study addresses empowerment of Muslim women through microfinance and self help groups in Chennai city of Tamilnadu. The information required for the study has been collected from both the primary and secondary sources. Further statistical analysis has been undertaken using various statistical tools like logistic regression, student t test, F test, Chi square test, ANOVA, Duncan Multiple Range Test (DMRT), the Wald Test, etc.